Will Xenotransplantation Ever Be Feasible? - Starzl, Thomas E. (1998)
In several recent conferences, the principal questions have been whether Xenotransplantation technology should be encouraged and, if so, how it should be regulated. Because the prospect of successful transplantation of animal organs into humans is still remote, the rush to achieve consensus about clinical application1,2 would be inexplicable were it not for two ostensibly unrelated issues. The first is the small but undeniable theoretical hazard of causing new human infections with the intermingling of tissues from different species. The second, advanced by animal-rights advocates, concerns the spiritual and ethical relationship of humans to animals.